Changes in Payment Timing in Canada's Large Value Transfer System - Nellie Zhang (Bank of Canada, 2015)
This paper uncovers trends in payment timing in Canada's Large Value Transfer System (LVTS) from 2003 to 2011. Descriptive analysis shows that LVTS payment activity has not been peaking in the late afternoon since 2008, and the improvement was most significant in 2009. Ordinary least squares regressions are conducted to identify various factors that might have contributed to the changes in the payment value time distribution. The main findings include that a larger proportion of high-value payments results in later payment submission and hence settlement; as an important source of intraday liquidity, a higher CDSX payout value tends to speed up LVTS transactions. Several changes in the system parameters - such as increases in the frequencies of the Jumbo algorithm and Jumbo queue expiry - also quickened the settlement. In addition, the results suggest that the temporary exceptional liquidity initiatives introduced in late 2008 and a large increase in settlement balances were major contributors to the earlier settlement of LVTS payments.
Keywords: G20; E50; 330; Payment clearing and settlement systems